(untitled) (Al-Academy, 2021)
The research is to identify the legend of the seven eyes amulet of Babylonian origin and the representations it carried of the link between the Babylonian past and the Islamic present presented in the design works of the promoted products, preserving its impact in the souls as a way to avoid the act of envy, and from this was the research problem that I want to get answers to, which That is (How was the legend of the seven-eyes amulet represented in the design of industrial products?), making its goal to identify how that legend was represented within the design work of marketed industrial products, and in order to reach the answer, the research presented many concepts starting with the legend in its various forms in industrial products. , and to identify the meaning of representation or simulation in design. From it, the researcher was able to reach the analytical axes to get the answer through the three deliberately selected samples, leading to the results. The most important thing in it is that all the samples were clear in expression and focus on the subject of the amulet is apparent in the samples. As for the representation, the means were clearly present, and the topics were represented in a relative manner, while the method of representation was fully realized. The most important conclusions were the Iraqi origin of the legend of the amulet, which was the focus of the focus in the overall construction of the design. As for the representations, the basis was to confirm the authenticity of its Iraqi origin and try to combine the concept of Babylonian envy and what it corresponds to in the subject within Islamic teachings